Impact of Social Media-Based Retail Investor Activity and Sentiment on Small-Cap Stock Behavior in Bali - Dananjaya, I Gusti Ngurah Agung; Prayudi, Made Aristia; Wiguna, I Gd Nandra Hary (E-Jurnal Akuntansi; Vol 35 No 7 (2025)DO - 10.24843/EJA.2025.v35.i07.p19, 2025)
The growing participation of retail investors in social media communities highlights the need to understand how their activities and sentiments influence stock market dynamics. This study aims to examine the effect of investor activity and sentiment on social media on trading volume and price volatility of small-cap stocks. A quantitative approach was employed, using a survey of 200 respondents actively involved in online investment communities. Data were analyzed using multiple linear regression. The results indicate that both investor activity and sentiment have a positive relationship with trading volume and price volatility. The regression models explain more than half of the variation in the dependent variables. This study concludes that social media plays a critical role as a space for shaping the behavior and investment decisions of retail investors in the digital stock market environment. Keywords: Retail Investor, Social Media, Sentiment, Trading Volume, Price Volatility